2013
DOI: 10.1111/cch.12113
|View full text |Cite
|
Sign up to set email alerts
|

Growing up with cerebral palsy: perceptions of the influence of family

Abstract: Health-care providers can contribute to the family's ability to facilitate quality of life by providing guidance on how to be advocates and teach advocacy, including the child with CP in family activities, accessing therapy and incorporating beneficial therapies at home, and promoting healthy sibling relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
6
0
3
Order By: Relevance
“…Meanwhile, there is a tendency toward family-centered services, in which the family work together with service providers to make informed decisions about the services and support the child and family receive (Law et al., 2003). This could potentially provide an increasing basis for the co-participation of the family and the therapist and, to a large extent, reduce challenges related to child care at home (Freeborn and Knafl, 2013; Law et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there is a tendency toward family-centered services, in which the family work together with service providers to make informed decisions about the services and support the child and family receive (Law et al., 2003). This could potentially provide an increasing basis for the co-participation of the family and the therapist and, to a large extent, reduce challenges related to child care at home (Freeborn and Knafl, 2013; Law et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, parents with other children reported higher scores in the Autonomy domain of their child with CP. In a qualitative study with female adults with CP that examined families and individual family member's contribution to overall QoL, one emergent theme was the importance of siblings as friends, mentors, instructors, and supporters in interaction during their time together in everyday life situations, including play ( 38 ). This interaction between siblings seems to reflect positively on parents' perceptions of their child autonomy, due to the opportunities to interaction and choices making with others.…”
Section: Discussionmentioning
confidence: 99%
“…A large family can also minimize the burden on parents regarding the care of their child with disabilities in everyday life activities ( 39 ). Healthy relationships with siblings in childhood can extend into adult life, positively influencing the QoL of a person with CP ( 38 ). Engagement of siblings in rehabilitation follow-up may allow us to hear their perceptions about family everyday life situations; questions about the diagnosis, intervention, follow-up; and as other informant about the QoL of the sibling with CP ( 13 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Selain itu, juga terdapat beberapa penelitian yang membahas tentang universal design, diantaranya penelitian Wahono dkk dalam [14], Wardani dalam [15], Anous dalam [2], Prellwitz dan Skär dalam [11] mengenai penerapan universal design pada produk, arsitektur sebuah bangunan maupun lingkungan. Beberapa penelitian yang membahas cerebral palsy diantaranya adalah penelitian Parkinson dkk dalam [9] mengenai rasa sakit yang diderita anak dengan cerebral palsy, penelitian Redford dalam [12] mengenai analisis kualitatif pengalaman anak-anak hidup dengan kondisi cerebral palsy dan penelitian dan Knalf dalam [5] mengenai pengaruh keluarga terhadap tumbuh kembang anak dengan cerebral palsy.…”
Section: Pendahuluanunclassified